Entre diamantes e cascalhos: a Escola Normal de Diamantina, 1878 a 1905 - Sousa, Gabriela Marques de (2021)
The following research is linked to the Graduate Program in Education at the Federal University of Uberlândia, along with the History and Historiography of Education area. As an object of investigation, The Escola Normal de Diamantina, between the years 1878 to 1905, was chosen. The research temporal delimitation is limited by the historical-institutional trajectory of the school itself, marked by its creation through the Brazilian Provincial Law no. 2,476 from November 9th, 1878, until the suspension of activities through Law no. 395 of November 23, 1904, ratified by Decree no. 1,778 of January 31st, 1905. The research's main focus was to understand if the installation, in 1879, as well as the closure of the Escola Normal de Diamantina, in 1905, was connected to the modern society project that had been delineating since the transitions between Empire and Republic. To this end, support was sought in the research of Araújo (2006; 2008), Goodwin Jr. (2007), Villela (2000; 2006; 2008), Nosella and Buffa (2005), Faria Filho (2000; 2015), Martins ( 2013), Souza (1993), Santos (2019), Berger (2000), Ribeiro (2009), Burity (2007), Le Goff (1992), among others, with the general objective of understanding how the Escola Normal de Diamantina was linked to Diamantina and Minas Gerais’s modernity movement between the end of the 19th century and the beginning of the 20th. The sources here used can be found in the Public Archives of Diamantina and Belo Horizonte - Biblioteca Antônio Torres and Arquivo Público Mineiro - as well as in the digital archives of the Hemeroteca Digital Brasileira and Center for Research Libraries; these are newspapers, collection of laws and decrees, messages, quotations, etc. Based on the connections between theoretical reference and the listed sources above, the following categories of analysis emerged: school institutions, Normal School, teacher training, education, progress, and modernity. Using a dialectical perspective as a core, in which it comprehends macro and micro scenarios of education, the methodology adopted in this work is aligned with the theoretical and methodological assumptions of research in the field of the history of education, based on documentary and bibliographic research. Therefore, the analyzes showed that Minas Gerais' public education problem during the 19th century was related to the lack of qualified primary education teachers associated with the high costs and low results generated by the Normal Schools maintained by the state public power, this being the emphasis of discussion in the empire-republic transition. Known as a continuance of the Normal education crisis in Minas Gerais, this situation, in the early years of the new regime, led to the gradual dismantling of public Normal education and to the suspension of the Escola Normal de Diamantina activity in 1905, which scope was the Catholic Church involvement through the assimilation of confessional educational institutions for teacher training and the creation of school groups by Minas Gerais state in 1906. That said, it can be confirmed that modernity in Minas Gerais followed the course of “progress” through the exchange between public and private sectors; these sought to solve the financial crisis as well as the need to found a society based on the ideals of the republic, from “progress” and modernity focused on education. It is ratified, therefore, that the suspension of the Escola Normal de Diamantina was associated with the intrinsic discourse to modernity, in which it was understood through the quarrel between the ancient and the modern to guarantee the development of Diamantina and Minas Gerais societies.